NAZEWNICTWO FORM AKTÓW PRAWA MIEJSCOWEGO - Szewc, Tomasz (Wydział Prawa i Administracji UAM, 2007)
The paper presents forms in which local laws are contained and characterises them. It also points out to some defects of existing regulations resulting form too many legal forms used by the legislature. Possible ways of unification of statutory solutions have been suggested.
TERMINOLOGY OF LEGAL INSTRUMENTS OF LOCAL LAW